Planning for the Development and Rehabilitation of the Sustainable Degraded Khmer Stone Sanctuary Site in Lao PDR Case Study: Archaeological Site “Tomo” Pathoumphone District, Champasak Province - VANIVONG, Khamphoupheth; SENGKHAMKHOUDLAVONG, Bouadam; SYHAVONG, Saikhim; SYHAVONG, Philasack; VENVONGTHONG, Phongeun; SENGONKEO, Luangphasy (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The Oup Moung (Wat Tomo) archaeological site is currently facing degradation over time and a lack of systematic development planning, which could jeopardize the nation’s invaluable historical significance. This study aims to establish guidelines for the sustainable development of the site, ensuring the preservation of cultural heritage alongside socio-economic growth. The research employs a mixed-methods approach, utilizing surveys to gather perspectives from local communities and relevant stakeholders. Research Objectives were 1) To study the historical value, architectural art, cultural landscape, and the potential for site development and restoration of the “Oup Moung” (Wat Tomo) archaeological site and 2)To explore guidelines for promoting heritage value, conservation models, and the sustainable restoration of the “Oup Moung” archaeological site and its surrounding areas. The findings reveal that the Oup Moung archaeological site possesses immense historical and cultural value, linked to ancient Khmer civilization, and is characterized by its unique “Hin Nam Nor” architecture and Pre-Angkorian artifacts. The most appropriate development approach is to elevate the site into a local museum that emphasizes the preservation of its original state through the Anastylosis restoration technique. Development should control the construction of facilities to ensure harmony with the natural environment and prioritize educational promotion to foster heritage awareness. This research proposes a balanced management model between conservation and cultural tourism. The recommendations serve as a crucial foundation for government agencies and relevant sectors in formulating management policies and strategic budget allocations, ensuring that development generates community income without compromising the nation's original cultural values.